Discovery of a Chlorophyll Binding Protein Complex Involved in the Early Steps of Photosystem II Assembly in Synechocystis . Issue 3 (28th March 2014) - Knoppová, Jana; Sobotka, Roman; Tichý, Martin; Yu, Jianfeng; Konik, Peter; Halada, Petr; Nixon, Peter J.; Komenda, Josef
Abstract : A complex of putative short-chain alcohol dehydrogenase Ycf39 and small membrane proteins related to the plant light-harvesting chlorophyll binding complexes was found to assist the early stage of cyanobacterial photosystem II assembly. The complex appears to deliver recycled chlorophyll to the newly synthesized D1 protein and to protect the protein against photodamage. Abstract: Efficient assembly and repair of the oxygen-evolving photosystem II (PSII ) complex is vital for maintaining photosynthetic activity in plants, algae, and cyanobacteria. How chlorophyll is delivered to PSII during assembly and how vulnerable assembly complexes are protected from photodamage are unknown. Here, we identify a chlorophyll and β-carotene binding protein complex in the cyanobacterium Synechocystis PCC 6803 important for formation of the D1/D2 reaction center assembly complex. It is composed of putative short-chain dehydrogenase/reductase Ycf39, encoded by the slr0399 gene, and two members of the high-light-inducible protein (Hlip) family, HliC and HliD, which are small membrane proteins related to the light-harvesting chlorophyll binding complexes found in plants. Perturbed chlorophyll recycling in a Ycf39-null mutant and copurification of chlorophyll synthase and unassembled D1 with the Ycf39-Hlip complex indicate a role in the delivery of chlorophyll to newly synthesized D1. Sequence similarities suggest the presence of a related complex in chloroplasts.